2020
DOI: 10.1002/jemt.23539
|View full text |Cite
|
Sign up to set email alerts
|

Holotomographic microscopy: A new approach to detect apoptotic cell features

Abstract: Holotomographic (HT) microscopy, combines two techniques, holography and tomography, and, in this way, it allows to quantitatively and noninvasively investigate cells and thin tissue slices, by obtaining three-dimensional (3D) images and by monitoring inner morphological changes. HT has indeed two significant advantages: it is label-free and low-energy light passes through the specimen with minimal perturbation. Using quantitative phase imaging with optical diffraction tomography, it can produce 3D images by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Recently, it was reported that DHT has a the potential to become an important diagnostics tool for the examination of different biological samples. 16,21,22 The obtained DHT results have brings a comparable quality to that of electron microscopy techniques, 24 which emphasizes the theoretical potential of this method in the vital imaging of nanostructures such as EVs. The aim of this study was to investigate the potential of the DHT method in imaging and the characterization of the 3D-RI distribution and morphology of single EVs to verify their heterogeneity and examine the influence of sample preparation procedures on the reconstructed RI data.…”
Section: Introductionmentioning
confidence: 62%
“…Recently, it was reported that DHT has a the potential to become an important diagnostics tool for the examination of different biological samples. 16,21,22 The obtained DHT results have brings a comparable quality to that of electron microscopy techniques, 24 which emphasizes the theoretical potential of this method in the vital imaging of nanostructures such as EVs. The aim of this study was to investigate the potential of the DHT method in imaging and the characterization of the 3D-RI distribution and morphology of single EVs to verify their heterogeneity and examine the influence of sample preparation procedures on the reconstructed RI data.…”
Section: Introductionmentioning
confidence: 62%
“…It is known that misregulation of apoptosis can lead to cancer or autoimmunity (Goldar et al, 2015; Singh et al, 2019). On the other hand, degenerative diseases occur when apoptosis increased (Carneiro & El‐Deiry, 2020; Salucci et al, 2020). Therefore, the researcher main goal is to develop promising cancer drugs addressed to enhance apoptotic inhibitors including Bcl‐2 family proteins and other substrates.…”
Section: Discussionmentioning
confidence: 99%
“…U937, a promonocytic human myeloid leukemia cell model, has been cultured as described by Salucci et al (2020) and its behavior has been monitored with the Inverted Microscopy (IM; Eclipse TE2000‐S Nikon; objective 10×).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, confirmation of whether nLifeact-GFP induced an alteration of the chromatin structure in living cells was further attempted by holotomography, which could observe biomolecules, such as chromatin and the cell membrane, but not actin filaments, with low-energy light passing through the specimen with minimal perturbation, by obtaining the refractive index (RI) distribution 41 . As shown in Figure 5e, in the nucleus of DOXOtreated p53 knockdown cells, the holographic images showed that several straight filament-like structures were formed by the expression of nLifeact-GFP but not by that of nAC-GFP, which colocalized with nLifeact-GFP and was detected by fluorescence imaging.…”
Section: Expression Of Nlifeact-gfp Modulates the Chromatin Structure...mentioning
confidence: 99%